Usefulness of ultrasound for assessing the primary tumor of hypopharyngeal carcinoma - Fukuhara, Takahiro (Laryngoscope Investig Otolaryngol, 2017)
OBJECTIVES: To clarify the usefulness of ultrasonography for detecting hypopharyngeal cancer. STUDY DESIGN: Cross‐sectional study. METHODS: The study included 95 patients who underwent pre‐treatment ultrasonography. We evaluated the usefulness of ultrasonography for detecting primary hypopharyngeal carcinoma of each T stage and subsite, and for assessing extrahypopharyngeal invasion. Additionally, we determined the efficacy of color Doppler for evaluating primary hypopharyngeal carcinoma. RESULTS: The patients comprised 93 men and 2 women with a mean age of 67.5 years. The T stage (primary tumors) was T1 in 29 patients, T2 in 22, T3 in 9, and T4 in 35. Primary sites with a T stage over T3 were detected using ultrasonography in 17 patients. Regarding primary subsites, postcricoid tumors were assessed most easily (64%), while posterior wall tumors were the most difficult to assess (25%). In 15 of 17 patients, the evaluation of extrahypopharyngeal invasion by ultrasonography matched up precisely with computed tomography findings. In addition, abnormally increased blood flow in primary hypopharyngeal cancers was recognized by color Doppler, and could be used to predict subsites. CONCLUSIONS: Cancers at T3 and T4 hypopharyngeal primary tumors and their extrahypopharyngeal invasion were detectable using ultrasonography. Furthermore, ultrasonography was useful for assessing postcricoid tumors that were difficult to observe by flexible laryngoscopy. LEVEL OF EVIDENCE: 4